Role of Heme Oxygenase-1 (HO-1) in the Pathogenesis of Hypertension among Young Adults: Association with Oxidative Stress, Inflammatory Markers, and Metabolic Profile - Maijidda Abubakar Musa; Kehinde Samuel Olaniyi; Abdulkadir Aminu Dauda; Stephanie Esosa Areloegbe; Sadiya Gambo Mustapha (Darul Yasin Al Sys, 2026)
Hypertension in young adults is increasingly recognized as a multifactorial condition associated with oxidative stress, inflammation, endothelial dysfunction, and metabolic imbalance. This study investigated the relationship between heme oxygenase-1 (HO-1) and hypertension among young adults, with particular attention to oxidative stress markers, inflammatory mediators, and metabolic profiles. A case–control study was conducted involving 170 hypertensive and normotensive participants. Sociodemographic and clinical characteristics were assessed alongside blood pressure, body mass index (BMI), body weight, and biochemical markers, including HO-1, vascular endothelial growth factor (VEGF), insulin, nitric oxide (NO), iron, and adenosine deaminase (ADA). Compared with normotensive controls, hypertensive participants had significantly higher systolic and diastolic blood pressure (p < 0.05), as well as higher BMI and body weight. HO-1 concentrations were markedly lower in hypertensive participants (p < 0.00001), indicating reduced antioxidant capacity. Conversely, VEGF concentrations were significantly elevated (p < 0.00001), consistent with altered vascular regulation. Hypertensive participants also exhibited increased insulin concentrations (p < 0.01), reduced NO concentrations (p < 0.00001), and elevated iron and ADA concentrations (p < 0.00001), collectively reflecting metabolic dysregulation, impaired endothelial function, oxidative stress, and inflammatory activity. Correlation analysis revealed no significant associations between HO-1 and adenosine, ADA, or xanthine oxidase (p > 0.05). These findings identify a distinct biochemical profile of young-adult hypertension characterized by reduced HO-1 and NO concentrations alongside increased VEGF, insulin, iron, and ADA concentrations. Although the case–control design does not establish causality, the results highlight HO-1 as a relevant component of the oxidative and vascular alterations associated with hypertension and support further longitudinal and mechanistic investigation.